Development of Taro Agribusiness Using Local Wisdom: a Swot Analysis to Promote Sustainable Food Security - Triyoso, Anang; Prihartini, Indah; Tain, Anas; Gunaisah, Endang (Pelopor Publikasi Akademika, 2025)
Taro shows promising agribusiness prospects as a local commodity that supports sustainable food security, but these efforts are still overshadowed by various obstacles that require the right handling strategy. The purpose of this research is to identify internal and external factors and develop a strategy for the development of taro agribusiness based on local wisdom in West Papua. This research uses a mixed-method design by combining surveys of 50 key informants, in-depth interviews, FGDs, observations, and SWOT analysis. The results of the study show the following factors: 1. Strengths include the availability of local seed varieties, suitable agroclimatic conditions, extensive land ownership, farming experience, and the position of taro as a local food for the community; 2. Weaknesses include limited production facilities, low financial capacity of farmers, simple processing technology, high transportation costs, and weak farmer institutions; 3. Opportunities include increasing market demand, support for regional autonomy, strategic production centers, and scientific and technological advances; and 4. Threats include low purchasing power, a high rate of product damage, weak legal certainty on land, land conversion, and competition with taro products from outside the region. This study concludes with a strategy that prioritizes strengthening production capacity, expanding market access, diversifying processed products through innovation, developing agroindustry, strengthening farmer institutions, improving production facilities, and implementing price regulation policies. The development of taro agribusiness requires a comprehensive strategy that integrates local wisdom to increase sustainable food security in West Papua.